KEPLER – NEWTON – LEIBNIZ – HEGEL : Portentous And Conflicting Legacies In Theoretical Physics, Cosmology And In Ruling Ideas - Malek, Abdul (JOURNAL OF ADVANCES IN PHYSICS, 2021)
Kepler’s Laws of planetary motion (following the Copernican revolution in cosmology), according to Leibniz and his follower Hegel, for the first-time in history discovered the keys to what Hegel called the absolute mechanics mediated by dialectical laws, which drives the celestial bodies, in opposition to finite mechanics in terrestrial Nature developed by mathematical and empirical sciences, but that are of very limited scope. Newton wrongly extended and imposed finite mechanics on the absolute mechanics of the cosmic bodies in the form of his Law of one-sided Universal Gravitational Attraction, by distorting and misrepresenting Kepler’s profound laws and in opposition to Leibniz’s more appropriate “Radial Planetary Orbital Equation”. The still-prevailing error by Newton (notwithstanding his well known manipulation of science for selfish ends), not only shows the limitation of mathematical idealism and prejudice driven modern cosmology in the form of Einstein’s theories of relativity; but also, have made gaining positive knowledge of the cosmos an impossibility and has impaired social/historical development of humanity by reinforcing decadent ruling ideas. Hegel’s Naturphilosophie is not only a protest against the misrepresentation of Kepler’s Laws in particular; his Enzyklopädie der Philosophischem Wissenschaften is the negation and the direct rebuttal of Newtonian physics and Philosophiæ Naturalis Principia Mathematica, in general. Modern natural science ignores Leibniz and Hegel at its own peril! Kepler’s phenomenological laws of planetary motion and the dialectical insights of Leibnitz and Hegel opens the way for gaining positive knowledge of the dynamics, structure and the evolution of the cosmic bodies and other cosmic phenomena; without invoking mysteries and dark/black cosmic entities, which has been the pabulum of official astrophysics and cosmology so far.